A kind of disassembled and reassembled, postmodern collective and personal self: Agency and the Insulin pump - Berk, Elizabeth (Journal of material culture, 2018)
This article examines the interaction between the Insulin pump, a biotechnology device used to treat type one diabetes, and the human to whom it is attached. It asks what kinds of selves the pump-human entanglement constitutes, and how these subjectivities shift the lived experience of agency. This article takes an auto-ethnographic approach, whereby the author marshals her own experiences as an Insulin pump-human entanglement to demonstrate her arguments. Ultimately, the article contends that being a pump-human entanglement entails an embodied cyborg subjectivity. This subjectivity produces an agent that, while structured in particular ways by entanglement with this technology, is ultimately more active in the mutual care accorded to her illness.